Country Economic Overview - Malawi Consulate (2017)
Country Economic Overview The Malawi economy is agro based with agriculture contributing 37% of the national GDP and employing 80% of the total workforce....
KerkoCite.ItemAlsoKnownAs: 2339240:84EBRSYI 2405685:KWAAJTHP

Malawi Growth and Development Strategy (MGDS-III) 2017–2022 - Government of Malawi (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:99BEMNP3 2405685:8AV66KVR

How (Not) to Fix Problems that Matter: Assessing and Responding to Malawi's History of Institutional Reform - Bridges, Kate; Woolcock, Michael (World Bank, 2017)
Malawi can be understood as a microcosm of institutional reform approaches in developing countries more broadly. A common feature of such approaches, whether implemented by government or donors, is reform initiatives that yield institutions that "look like" those found in higher-performing countries but rarely acquire the same underlying functionality. This paper presents a retrospective analysis of previous institutional reform projects in Malawi, as well as interviews with Malawi-based development practitioners. The paper finds a plethora of interventions that, merely by virtue of appearing to be in conformity with "best practices" elsewhere, are deemed to be successful yet fail to fix underlying problems, sometimes in contradiction to internal and public narratives of positive progress. This unhappy arrangement endures because a multitude of imperatives, incentives, and norms appear to keep governments and donors from more closely examining why such intense, earnest, and long-standing efforts at reform have, to date, yielded so few successes. This paper seeks to promote a shift in approach to institutional reform, offering some practical recommendations for reform-minded managers, project teams, and political leaders in which the focus is placed on crafting solutions to problems that Malawians themselves nominate, prioritize, and enact.
Accepted: 2017-12-29T15:36:13Z KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8289 2339240:5IPEVBSQ 2405685:AT78SWY3 4656463:P3GHJI3Y
Keywords: Capacity Building; Civil Service; Development Effectiveness; Governance; Institutions; Legitimacy; Public Administration; Public Sector; Reform

Tiyende! Let’s Walk! - Save the Children (2017)
Singilton Phiri Interactive Radio Instruction Specialist Save the Children in Malawi June 16, 2017 Before the introduction of sponsorship in rural Zomba in Malawi, walking...Read the full article...
KerkoCite.ItemAlsoKnownAs: 2339240:2DF274TB 2405685:IEJHUQ7J

Moving Teachers to Malawi's Remote Communities: A data-driven approach to teacher deployment - Asim, Salman; Chimombo, Joseph; Chugunov, Dmitry; Gera, Ravinder (World Bank, 2017)
KerkoCite.ItemAlsoKnownAs: 2405685:G3BXG2DZ 2486141:URBUWVJ8

Moving teachers to Malawi's remote communities: A data-driven approach to teacher deployment - Asim, Salman; Chimombo, Joseph; Chugnov, Dmitry; Gera, Ravinder (World Bank, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:27XHDSI8 2339240:TQFW4ACB 2405685:CLQLKA7M 2405685:K4RZX8TC

Low-cost, familiar tech for teacher support: Evidence from a SMS campaign for early grade teachers in Malawi - Kipp, S (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:87KJQVTK

Assessing the Impact of Early Learning Programs in Africa - Gove, Amber; Brunette, Tracy; Bulat, Jennae; Carrol, Bidemi; Henny, Catherine; Macon, Wykia; Nderu, Evangeline; Sitabkhan, Yasmin (New Directions for Child and Adolescent Development, 2017)
We present results from early learning programs in six African countries: Ethiopia, Kenya, Liberia, Malawi, Tanzania, and Uganda. In partnership with ministries of education, RTI International has worked within government systems to support the design and deployment of locally contextualized materials, training, and assessment tools, with the goal of improving outcomes for early learners in primary schools, and in Kenya and Tanzania preprimary as well. Here we report on the experience and evidence of impact from specific programs in each country, including summary assessment results when available. In several countries with completed impact evaluations, there are significant and important learning gains of between 0.2 and 2.57 SD in effect size; in one case the percentage of students reaching grade‐level reading proficiency increased from 12% to 47%. In the context of increased urgency surrounding what UNESCO has called a “global learning crisis,” these experiences provide useful lessons for policymakers and practitioners alike.
shortDOI: 10/gf86mm KerkoCite.ItemAlsoKnownAs: 10.1002/cad.20224 10/gf86mm 2405685:B4LHC2GD